A new condensed freshwater-brackish water bivalve-dominated assemblage in the Aptian Crato Formation, Araripe Basin, NE Brazil and its paleoenvironmental significance - da Silva, Victor R. [UNESP]; Varejão, Filipe G.; Matos, Suzana A.; Rodrigues, Mariza G. [UNESP]; Warren, Lucas V. [UNESP]; Assine, Mário L. [UNESP]; Fürsich, Franz T.; Simões, Marcello G. [UNESP] (Elsevier, 2024)
The known occurrences of Early Cretaceous freshwater bivalves in the Araripe Basin are confined to the 0.85- to 2-m-thick Caldas Bed of the Crato Formation. Herein, we record a new bivalve-dominated assemblage in a siltstone bed nearly 30 m below the upper boundary with the overlying Romualdo Formation. The assemblage is composed of ecologically incompatible bivalve mollusk species, being dominated by tiny individuals of Modiolus? sp., a brackish water form. These are directly associated with the freshwater bivalves Araripenaia elliptica and Monginellopsis bellaradiata, the latter two species commonly found in the Caldas Bed. Those bivalves are mixed with carbonized, partially comminuted plant remains. Specimens of Modiolus? sp. are usually articulated and are dispersed to loosely packed or forming cm-long clusters. A few shells of the freshwater forms are also articulated. The bivalves lived in a semi-confined embayment setting with fluctuating salinity. Background brackish water conditions must have existed long enough for the Modiolus? sp. larvae to settle and develop as juvenile individuals. Rapid salinity fluctuations associated with sea level and climate variations allowed A. elliptica and M. bell aradiata to thrive in the same area. Hence, the numerically dominant shells of the brackish water forms and the freshwater bivalves have been telescoped into the same bedding plane, generating an environmentally condensed, time-averaged benthic assemblage. Finally, the presence of these taxa considerably expands the vertical/temporal distribution of bivalve mollusks within the Crato Formation.